PKM Pendampingan Belajar Konsep Operasi Hitung Bilangan Asli Menggunakan Alat Peraga Papan Operasi Hitung Bilangan Asli - Shofia Hidayah; Lailatul Fajriyah; Siti Aisyah; Diana Susilowati (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The purpose of this service is to describe initiatives that can be done to increase students' interest in learning mathematics, especially in the material of natural number calculation operations. The solution offered in this activity is assistance in learning the concept of natural number counting operations using natural number calculation operation board props. Participants in this service activity involved 28 students of grade III MI Miftahul Islam. The stages of this activity consist of three stages, namely the preparation, implementation, and evaluation stages. The conclusion obtained from this service activity is that assistance in learning the concept of natural number counting operations using natural number calculation operation board props is said to have succeeded in increasing students' interest in learning mathematics. This is evidenced by the increase in the percentage of students who achieve scores above KKM (Minimum Completeness Criteria) after mentoring, from 30% to 85%.